Qualitative methods for practice research - Longhofer, Jeffrey L. (Jeffrey Lee); Floersch, Jerry; Hoy, Janet (New York ; Oxford : Oxford University Press, 2012)
By generating knowledge of practice in open and natural systems qualitative methods can be used to examine how practice is experienced and how interventions may be understood and transformed. This guide will equip practitioner-scholars with the foundation for conducting research that makes a difference.
Description based on online resource; title from PDF title page (viewed on Aug. 13, 2012).
Includes bibliographical references and index.
Keywords: Social service -- Research -- Methodology; Qualitative research